The pathogenesis of influenza virus infections: the contributions of virus and host factors - Fukuyama, Satoshi; Kawaoka, Yoshihiro (Current opinion in immunology, 2011)
► The pathogenicity of influenza A virus (IVA) depends on interactions between virus and host proteins. ► Among the viral proteins, HA is responsible for determining the target animal species, organs, and cell-types for IVA. ► The NS1 protein of IVA inhibits IFN-I production in virus-infected cells by interfering with the RIG-I signaling pathway. ► Pulmonary macrophages induce epithelial cell apoptosis, which is mediated by the TRAIL-DR6 interaction in the IVA-infected lung. Influenza viruses cause acute respiratory inflammation in humans and symptoms such as high fever, body aches, and fatigue. Usually these symptoms improve after several days; however, the 2009 pandemic H1N1 influenza virus [influenza A(H1N1) 2009] is more pathogenic than seasonal influenza viruses and the pathogenicity of highly pathogenic H5N1 viruses is still higher. The 1918 influenza pandemic virus caused severe pneumonia, resulting in an estimated 50 million deaths worldwide. Several virulence factors have been identified in these virus strains, but host factors are also responsible for the pathogenesis of infections caused by virulent viruses. Here, we review the contributions of both virus and host factors to the pathogenesis of these viral infections.